2018
DOI: 10.1038/s41525-018-0074-3
|View full text |Cite
|
Sign up to set email alerts
|

Rare TP53 variant associated with Li-Fraumeni syndrome exhibits variable penetrance in a Saudi family

Abstract: Li-Fraumeni syndrome (LFS) is an inherited, autosomal-dominant condition that predisposes individuals to a wide-spectrum of tumors at an early age. Approximately 70% of families with classic LFS have pathogenic variants in the tumor suppressor gene TP53 that disrupt protein function or stability. While more than 70% of pathogenic variants in TP53 are missense variants, the vast majority occur very infrequently, and thus their clinical significance is uncertain or conflicting. Here, we report an extremely rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…At the protein level, the revealed c.645del variant causes a frameshift with the introduction of a premature stop codon within the p53 DNA binding domain (DBD) (p.Ser215Argfs * 32). The DBD domain, located in the central part of the p53 protein, contains most of the LFS-associated missense variants (Bouaoun et al, 2016 ; AlHarbi et al, 2018 ). However, also frameshift pathogenic variants in the p53 DBD, such as c.685dup (p.Cys229Leufs * 11), have been observed in a family with LFS (Ji et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the protein level, the revealed c.645del variant causes a frameshift with the introduction of a premature stop codon within the p53 DNA binding domain (DBD) (p.Ser215Argfs * 32). The DBD domain, located in the central part of the p53 protein, contains most of the LFS-associated missense variants (Bouaoun et al, 2016 ; AlHarbi et al, 2018 ). However, also frameshift pathogenic variants in the p53 DBD, such as c.685dup (p.Cys229Leufs * 11), have been observed in a family with LFS (Ji et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe a family carrying a novel pathogenic germline variant of the TP53 gene. This inherited frameshift variant is extremely rare because more than 70% of the pathogenic TP53 variants in LFS families were observed to be missense variants (AlHarbi et al, 2018 ). This family case report highlights the importance of offering genetic counseling and genetic testing to all family members at high risk to be carriers of TP53 inherited pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, germline TP53 p.I254V mutations causing p53 inactivation were found in two unrelated uveal melanoma patients (Hajkova et al 2018). Approximately 70% of TP53 pathogenic variants in LFS arise as missense mutations interspersed in six "hotspot" regions of the DNA binding domain (Leroy, Anderson, and Soussi 2014;AlHarbi et al 2018).…”
Section: J O U R N a L P R E -P R O O F Tumor Protein 53 (Tp53)mentioning
confidence: 99%
“…More recently, germline TP53 p.I254V variants causing p53 inactivation were found in two unrelated patients with UM ( Hajkova et al., 2018 ). Approximately 70% of TP53 pathogenic variants in LFS arise as missense variants interspersed in six hotspot regions of the DNA-binding domain ( AlHarbi et al., 2018 ; Leroy et al., 2014 ). For such patients, routine skin examinations should be considered alongside interdisciplinary clinical management.…”
Section: Defined Mixed-tumor Syndromes With Increased Melanoma Riskmentioning
confidence: 99%
“…The authors also observed this variant in an additional, unrelated individual with colon, breast and ovarian cancer, indicating the potential relevance of this variant to multiple types of cancer in this population. A second study reports on a 5-year-old female, whose data is also included in this study, with glioblastoma multiforme and constitutional mismatch repair-deficiency due to an MSH6 homozygous c.1883G>A mutation, who continued to experience an exceptional and durable response, 9 months later, to the immune checkpoint inhibitor (ICPI) nivolumab [ 48 ]. To the authors’ knowledge, this was the first report in the Arab world of a durable response to ICPIs in a pediatric glioblastoma patient.…”
Section: Introductionmentioning
confidence: 99%